The Role of Public Relations in Disseminating Government Programs Through Social Media - Irawanto; Riky Wellil Saputra; Hadi Hidayat; Semuel Risal (East Asian Journal of Multidisciplinary Research, 2022)
The objectives to be achieved in this research are to: (1) analyze the role of Public Relations and Protocol in disseminating Government programs through social media at the Regional Secretariat of Hulu Sungai Utara Regency (2) identify the obstacles faced by Public Relations and Protocol in disseminating Government programs through social media in The Regional Secretariat of Hulu Sungai Utara Regency and (3) provide solutions to overcome the obstacles faced by Public Relations and Protocol in disseminating Government programs through social media at the Regional Secretariat of Hulu Sungai Utara Regency. This study used descriptive qualitative method. The data obtained from the informants in this study were: Head of the Public Relations and Protocol Section of the Hulu Sungai Utara Regency (Informant), Head of the Documentation and Publication Subdivision at the Public Relations and Protocol Section of the Regional Secretariat of Hulu Sungai Utara Regency (Key Informant), Staff of the Public Relations and Protocol of the Regional Secretariat of the North Hulu Sungai Regency. Data collection techniques are Interview, Observation and Documentation. The research data were analyzed descriptively qualitatively. The results of the study show (1) The role of public relations and protocols in the socialization activities of the Hulu Sungai Utara Regency Government program which includes development, governance and public services through social media has been running optimally, but still not all of them can be implemented according to organizational goals, (2) Constraints faced Public Relations in disseminating Government Programs through social media at the Regional Secretariat of Hulu Sungai Utara Regency in the form of: not fulfilling the quantity of public relations officers who handle the socialization of Government programs through social media, Not yet mastered by their work due to minimal educational background and training and completeness of public relations work facilities that are still not yet available as needed (3) solutions to overcome obstacles faced by public relations in disseminating Government programs through social media at the Regional Secretariat of Hulu Sungai Utara Regency are needed: additional formation of public relations officers, increasing education education and training related to public relations, improving coordination between the head of public relations and protocol with documentation and publication officers and completing work facilities for information purposes. Keywords: Disseminating Government Programs, Social Media, Public Relation, Role Of Public Relation